2015
DOI: 10.1080/02640414.2015.1085077
|View full text |Cite
|
Sign up to set email alerts
|

Lumbopelvic motor control and low back pain in elite soccer players: a cross-sectional study

Abstract: This study aimed to investigate the relationship between the history of low back pain and quality of lumbopelvic motor control in soccer players. Forty-three male elite soccer players (mean age, 18.2 ± 1.4 years) filled in questionnaires related to low back pain and attended a session to assess lumbopelvic motor control by means of five tests (the bent knee fall out test, the knee lift abdominal test, the sitting knee extension test, the waiter's bow and the transversus abdominis test). A physiotherapist, blin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 39 publications
0
34
0
7
Order By: Relevance
“…Then, the differences in the activity-profile from each position may explain why there were positional differences in G-forces in match play. In consequence, the development of position-specific training drills considering the trunk inclination and G-forces experienced by the players is necessary to prepare not only for the physical demands (e.g., training trunk flexion postures with constant G-forces, which may avoid low back pain) [ 12 ] but also for successful performance in the field of regard [ 10 , 16 ]. However, this consideration does not seem to be so important for the locomotor efficiency ratio since no positional differences were found, which confirms the results reported by a previous investigation [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, the differences in the activity-profile from each position may explain why there were positional differences in G-forces in match play. In consequence, the development of position-specific training drills considering the trunk inclination and G-forces experienced by the players is necessary to prepare not only for the physical demands (e.g., training trunk flexion postures with constant G-forces, which may avoid low back pain) [ 12 ] but also for successful performance in the field of regard [ 10 , 16 ]. However, this consideration does not seem to be so important for the locomotor efficiency ratio since no positional differences were found, which confirms the results reported by a previous investigation [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the declines in physical performance have been linked to a depletion of muscle glycogen towards the end of the match [ 26 , 35 ]. These observations have significant practical implications for strength and conditioning coaches since the resistance to fatigue needs to be trained through trunk strength exercises, trunk mobility (e.g., spine sparing exercises) in addition to lumbopelvic control exercises [ 12 , 36 ]. However, match half did not significantly affect the locomotor efficiency ratio of the players and these results are in line with the only investigation on this ratio available to date [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been suggested that for the functional evaluation of the trunk and lumbo-pelvic-hip complex, dynamic hip-pelvic movement patterns should be investigated [10]. Previous research has identified differences between youth athletes with and without LBP on lumbo-pelvic-hip complex movement patterns [11][12][13][14] and an association between LBP and frontal plane hip-pelvic movement patterns has been observed in single-leg dynamic tasks in youth cricket players [15] and in adults with LBP [16].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the trunk kinematics have a significant effect on knee and hip energetics in running [ 7 ], hamstring injury [ 8 ], patellofemoral joint stress [ 9 ], and low back pain in professional soccer players [ 10 ]. For instance, a previous study found that upright trunk posture in running was associated with greater patellofemoral joint stress than running with forward trunk flexion [ 9 ].…”
Section: Introductionmentioning
confidence: 99%